PARODI CALON ARANG DALAM NOVEL JANDA DARI JIRAH KARYA COK SAWITRI - Mulyawati, Netari; Rahayu, Lina Meilinawati; Saidi, Acep Iwan (JURNAL PESONA, 2017)
This research described characters parody in the novel Janda dari Jirah by Cok Savitri. Parodi appears indicating that the glorification of Calon Arang. This research method uses descriptive analytical with the theory of parody as part of intertextuality. Parody which appears also associated with feminine and masculine leadership style defined by Parker. This study shows that there is a glorification through figures and depictions of feminine leadership style Candidate Arang.